Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

-3/4(8n+12)=3(n-3) show work pls

Sagot :

Answer: n = 0

Step-by-step explanation:

Given expression

(-3/4) (8n + 12) = 3 (n - 3)

Expand parentheses and apply the distributive property

-6n - 9 = 3n - 9

Add 9 on both sides

-6n - 9 + 9 = 3n - 9 + 9

-6n = 3n

Subtract 3n on both sides

-6n - 3n = 3n - 3n

-9n = 0

Divide -9 on both sides

-9n / -9 = 0 / -9

[tex]\boxed{n=0}[/tex]

Hope this helps!! :)

Please let me know if you have any questions

Answer:

0

Step-by-step explanation:

-3/4(8n+12)=3(n-3)

-24/4n-36/4=3n-9

-6n-9=3n-9

-6n-3n-9=-9

-9n-9=-9

-9n=-9+9

-9n=0

n=0/-9

n=0

Please mark me as Brainliest if you're satisfied with the answer.